Blunted Arousal in Response to Psychological Stress is Associated with Current Suicide Ideation. (31st August 2020) - Chesin, Megan; Cascardi, Michele; Tsang, William; Smith, Samantha
Abstract : The purpose of this study was to test the association between arousal in response to psychological stress, as measured by standardized maximum decrease in high-frequency heart rate variability (HF HRV) during a stressful laboratory task, and current suicide ideation (SI). 81 emerging adult college students completed a stressful laboratory task consisting of the computerized Stroop and Cyberball while having their heart activity recorded. Spectral analysis and Fast Fourier transformations were used to decompose and transform the recording into the high (0.15 Hz–0.4 Hz) frequency component. After the task, participants completed the Beck Scale for Suicide Ideation to measure current SI, the Beck Depression Inventory-II to assess depressive symptom severity, and a brief medical history. Multivariate negative binomial regression analysis showed that the negative association between SI and arousal in response to psychological stress remained statistically significant when suicide attempt history, depressive symptom severity, female gender, and current smoking behavior were controlled. Identification of potential biomarkers for SI is important for suicide behavior prevention given limits to self-report SI assessment. Our results suggest arousal in response to psychological stress merits further consideration as a biomarker for current SI.